Feline Panleucopenia in Bengal Cats at Hasanuddin University Animal Educational Hospital: Feline Panleucopenia Virus - Sarmadana, Mirva; Dian Fatmawati; Musdalifah (Hasanuddin University, 2023)
Feline panleukopenia is an infectious disease that attacks cats, especially cats that have not been vaccinated at a young age. The main cause of this disease is feline panleukopenia virus which belongs to the Parvoviridae family. Panleukopenia virus is a non-enveloped single-stranded DNA virus and can cause fever, hemorrhagic gastroenteritis, leukopenia, vomiting, depression, dehydration and diarrhea with a high mortality rate. The purpose of writing this case study is to determine the description and treatment of the disease in cases of feline panleukopenia in cats using diagnostic methods including history taking, physical examination and further examination. The results of the physical examination showed that the cat had decreased appetite. Body weight was 2.6 kg and rectal temperature was 38.6 °C. The patient also experienced dehydration which was indicated by checking skin turgor which reached >2 seconds and visible nictitans membranes. Then, inflammation of the ears, anorexia, vomiting and diarrhea were found. Treatment is carried out by administering fluid therapy, antibiotics, anti-diarrhea, anti-vomiting and multivitamins.